COVID-19 Vaccine Hesitancy among Adults in India: A Systematic Review and Meta-analysis - M. D. Sangeetha; P. K. Sreenath Menon; Bhalangki Kupar Kharmawphlang; Darshan Hoysanahalli Shivashankarappa; Sharath Burugina Nagaraja (Indian Journal of Public Health)
The global health crisis triggered by the SARS-CoV-2 in 2019, known as the COVID-19 pandemic, prompted vaccination drives worldwide, including in India, to address the crisis. However, vaccine hesitancy remains a significant challenge to achieving vaccination goals. Hence, we conducted a systematic review and meta-analysis during 2021–2023 to estimate the prevalence of COVID-19 vaccine hesitancy among adults in India and identify associated factors. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. Quality assessment was performed using the Joanna Briggs Institute checklist. Pooled prevalence estimates were calculated using a random-effects model. A total of 265 articles were identified, of which 21 full-text articles were included in the review. The pooled estimated prevalence of COVID-19 vaccine hesitancy among adults in India was found to be 28% (95% confidence interval: 27–29). Subgroup analysis revealed variations in hesitancy rates across different states, with higher rates observed in Jammu and Kashmir (44%), West Bengal (49%), and Maharashtra (39%). Gender-based analysis indicated higher hesitancy among males (36%) compared to females (26%). Among different study populations, medical students showed the lowest hesitancy rate (13%), whereas the general population exhibited the highest (34%). The findings suggest that vaccine hesitancy remains a significant concern in India, with one in four adults expressing hesitancy toward COVID-19 vaccination. Hesitancy rates vary across states, genders, and study populations. Addressing the factors contributing to hesitancy, such as safety concerns, lack of evidence, and misinformation, is crucial to enhance vaccine acceptance.